Domination or empowerment?: a power discourse analysis of 1 and 2 Corinthians - Cen, Esther G. (Pickwick Publications, 2023)
"This book argues that Paul, as God's accountable steward, seeks not to dominate the Corinthians but to empower them to mature in their understanding and conduct themselves appropriately under the cruciform authority of Jesus Christ. It invites readers to revisit the merely negative notion of power in deconstructionist power discourses and reconsider the importance of good uses of power in building up a faith community." --